Experiences of Mexican teenage students when choosing a math degree: A mathematical narrative identity study - Martínez-Sierra, Gustavo; Cervantes-Barraza, Jonathan; Jiménez-Sandoval, Lorena (Uniciencia, 2021)
There is little qualitative research on mathematics education focused on the experiences of young students when choosing a mathematics degree and how these experiences are assimilated into their mathematics life stories. The objective of this narrative inquiry is to identify the experiences of Mexican students who choose a mathematics degree through their mathematics life story. The conceptualization of a mathematical narrative identity divided into motivations, sources of motivation, and expectations allowed the identification of the following: (1) motivation of Mexican students for choosing a math degree, (2) sources of this motivation, and (3) future expectations related to this choice. This qualitative study was conducted based on a case study to prepare an in-depth analysis of multiple cases and frame them into a general description. Data was gathered from 47 interviews to collect students’ mathematics life stories. The four thematic analyses gave the following results: (1) the three main motivations were “liking mathematics”, self-efficacy belief, and the desire to become a “good teacher”, (2) the two main expectations were “being a good teacher” and “learning more mathematics”, and (3) the four main sources of motivations were self-efficacy belief, having “good teachers”, indirect experiences, and mastering knowledge. Results have similarities with the importance of self-efficacy beliefs and differences between “liking mathematics” and the desire to become a “good teacher” regarding the psychological explanations about the motivational forces to choose a math degree.